Hybrid vigor in cytoplasmic geneic male sterility system-based hybrids for seed yield and its associated traits in pigeonpea [Cajanus cajan (L.) Millsp.] - Patel, P.T.; Tikka, S.B.S. (The Indian Journal of Genetics and Plant Breeding, 2017)
Six newly converted cytoplasmic male sterile lines were crossed with 12 fertility restorer lines in line x tester mating design. Synthesized hybrids were evaluated with check Gujarat Tur Hybrid 1 at Sardarkrushinagar, Jagudan and Khedbrahma to study the extent of heterosis. Analysis of variance in individual and across the environments revealed significant difference among genotypes and existence of overall heterosis for seed yield/plant. High heterosis was recorded for grain yield/plant, pods/plant and harvest index, while, medium heterosis for plant height, number of branches/plant, 100-seed weight, protein content, biological yield and reproductive period. Days to flowering, days to maturity, number of seeds/pod and pod length recorded low magnitude of heterosis. Five hybrids, namely, CMS GT 087A x GTR 0525 (116.40%) CMS GT 087A x AGTR 534 (108.93%), CMS GT 0307A x AGTR 0538 (99.21%), CMS GT 0301A x AGTR 0534 (95.51%) and CMS GT 0308A x AGTR 0536 (89.32%) showed standard heterosis for grain yield and its component characters.